The Sorceress and the friar - Schiffman, Suzanne; Berger, Pamela C.; Karyo, Tchéky, 1953-; Boisson, Christine, 1957-; Carmet, Jean.; Mystic Fire Video (New York, NY. : Mystic Fire Video, 1987)
Story of medieval life and faith in 13th-century France, which centers on the confrontation between a forest woman and healer and the righteous Dominican friar sent by the Pope to her village as an inquisitor to seek out heretics.
VHS format.
English language version.
Title on container and label: Sorceress.
Videocassette release of the 1988 motion picture.
Original motion picture filmed simultaneously in English and French.
Director, Suzanne Schiffman ; producers, Pamela Berger, Annie Leibovici, Georges Reinhart ; scenario, Pamela Berger, Suzanne Schiffman ; story by Pamela Berger.
Keywords: Inquisition -- France -- Drama; Feature films